2015
DOI: 10.1080/07391102.2015.1080629
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous behavior of metalloproteins toward metal ion binding and selectivity: insights from molecular dynamics studies

Abstract: About one-third of the existing proteins require metal ions as cofactors for their catalytic activities and structural complexities. While many of them bind only to a specific metal, others bind to multiple (different) metal ions. However, the exact mechanism of their metal preference has not been deduced to clarity. In this study, we used molecular dynamics (MD) simulations to investigate whether a cognate metal (bound to the structure) can be replaced with other similar metal ions. We have chosen seven diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The mechanism of PZA catalysis by Mycobacterium tuberculosis PZase is centered on deprotonation of the C138 thiol group, which is stabilized and activated by K96 and D8, respectively . Both experimental and theoretical studies have indicated that altering Fe 2+ /Zn 2+ with other divalent metal ions, such as Mn 2+ , Co 2+ , Sr 2+ , Ba 2+ , Fe 3+ , Mg 2+ , and Ca 2+ , cannot strongly change the activity and stability of PZase, that is, the enzyme shows stability coordinating each of the ions at the MCS. A rare cis‐peptide bond exists in PZase between I133 and A134, making possible the formation of an oxyanion hole between the amine group of A134 and C138, which is also observable in pyrazinamidase from P. horikoshii and Acinetobacter baumanii .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of PZA catalysis by Mycobacterium tuberculosis PZase is centered on deprotonation of the C138 thiol group, which is stabilized and activated by K96 and D8, respectively . Both experimental and theoretical studies have indicated that altering Fe 2+ /Zn 2+ with other divalent metal ions, such as Mn 2+ , Co 2+ , Sr 2+ , Ba 2+ , Fe 3+ , Mg 2+ , and Ca 2+ , cannot strongly change the activity and stability of PZase, that is, the enzyme shows stability coordinating each of the ions at the MCS. A rare cis‐peptide bond exists in PZase between I133 and A134, making possible the formation of an oxyanion hole between the amine group of A134 and C138, which is also observable in pyrazinamidase from P. horikoshii and Acinetobacter baumanii .…”
Section: Introductionmentioning
confidence: 99%
“…Gogoi et al . investigated protein-metal ion binding affinities by analysing MD simulations of 49 different cation-protein complexes 6 . Metal cations can alter peptide structure by interacting with backbones and thereby enforcing non-Ramachandran geometries 7 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Metal coordination chemistry requires the use of quantum mechanics (QM) simulations, for the traditional force fields have not been able to completely address the chemistry around these metal co-factors [29]. Previous study has identified the presence/absence of metal binding selectivity in various type of divalent metal metalloproteins using molecular dynamics simulations, this approach, however, does not provide enough accuracy in comparisons of structural differences induced by different divalent metal cofactors [30]. Density functional theory (DFT) has been applied to the studies of protein, which provides sufficient computational efficiency as well as accuracy.…”
Section: Plos Onementioning
confidence: 99%